Influence of competitive attitude and self-efficacy on task motivation in vocational high school students: the moderating role of competitive environment in the context of ‘Lying Flat’ culture - Ma, Cheng; Chen, Bo-Ching (Frontiers in Psychology, 2024)
In recent years, 'lying flat' has emerged as a significant term in contemporary discourse, referring to the phenomenon where modern young people choose passive resistance due to a lack of motivation when facing various situations. These trends have the potential to diminish the future learning enthusiasm and holistic development of vocational high school students, thus impacting their competitiveness in the future job market. Methods: This study employs a motivational model for vocational high school students based on self-efficacy theory and person-environment fit theory to explore whether the competitive atmosphere moderates the impact of self-efficacy and competitive attitudes on task motivation. Using a secondary data research approach, the study analyzed a sample of 944 Taiwanese vocational high school students from the 2018 Programme for International Student Assessment (PISA) dataset with Partial Least Squares Structural Equation Modeling (PLS-SEM).The results indicate that self-efficacy and competitive attitudes positively influence task motivation. Additionally, self-efficacy not only enhances competitive attitudes but also indirectly influences task motivation through the mediation of competitive attitudes. The study also revealed that the moderating effect of the competitive environment was not statistically significant in the overall sample. Further multiple-group comparisons between male and female vocational high school students showed no significant differences in most paths, but gender differences emerged in the positive moderating effect of the competitive environment on the influence of competitive attitudes on task motivation.These findings suggest that in cultivating task motivation among vocational high school students, interventions should be tailored to accommodate the differing responses of male and female students. For female students, providing more opportunities for teamwork and utilizing collaborative approaches to cope with the competitive environment may enhance task motivation. Conversely, for male students, enhancing self-efficacy and stimulating intrinsic competitive attitudes may be more effective. Addressing these differences could potentially reduce the occurrence of the 'lying flat' phenomenon among vocational high school students in the future.